Seasonal differences in plankton community structure are more pronounced than spatial patterns in the headpond and downstream portions of a large impounded river. Issue 3 (3rd July 2019) - Nguyen, Huy Q.; Curry, R. Allen; Monk, Wendy A.; Culp, Joseph; Linnansaari, Tommi
ABSTRACT: Plankton community samples from a reservoir were compared to samples from a river downstream of a large hydroelectric generating station on the lower Saint John River, New Brunswick, Canada. The study focused on spatiotemporal variation of the plankton communities and their association with physicochemical parameters in the reservoir–downstream river system after almost 50 years of limnological evolution. The survey revealed 288 phytoplankton and 85 zooplankton taxa, dominated in abundance by rotifers and Cyanobacteria. The taxa richness was significantly greater than reports at the time of the reservoir creation. Spatial variability of the plankton community in the reservoir was statistically homogeneous among sites and the water layers across sites during its stratified period. The river plankton communities followed the same patterns as the reservoir, and river sites were always statistically similar to the reservoir community in terms of richness and abundance. The similarity of the communities across the reservoir and the river was highest during summer. Influential variables explaining seasonal differences in phytoplankton and zooplankton communities included physical, nutrient, and biotic factors. Our study demonstrates how a large, run-of-the-river hydroelectric generating station can regulate the plankton community up to 20 km downstream.